The effect of 6-prism base-out at 6-metre fixation on vergence and accommodation systems - Abu Bakar, Nur Munirah; Ithnin, Mohd. Hafidz (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: Prisms is used for binocularity diagnosis and vision therapy in optometry particularly in treating symptomatic vision anomalies such as divergence excess, convergence insufficiency, nystagmus and concomitant as well as incomitant strabismus. This utilization of base-out prism in the alteration of vergence and accommodation system is not well explored especially on normal binocular vision. This study aimed to assess the effect of prism base-out inducement on vergence and accommodation among normal binocular vision system. Aim: To compare the value of positive fusional vergence (PFV) and amplitude of accommodation (AA) before and after introduction of 6 prism base-out (BO) at fixation distance of 6m for 15 minutes. Methodology: Thirty participants were recruited in this quasiexperimental study and all of the participants wore the 6 prism BO for 15 minutes while watching movie at 6m. AA and PFV at 6m and 40cm were measured pre- and post-watching movie at 6m with 6 prism BO inducement. Results: The AA and PFV before and after intervention were then being compared and the results showed that there were insignificant changes (p>0.05) in AA and PFV of both eyes. Conclusion: The results suggested that the utilization of 6 prism BO in 15 minutes did insignificantly alter accommodation and vergence system.